The Madrid Nomenclature Section: outcomes and important changes to the Code following the XXth International Botanical Congress - Klopper, Ronell; Muasya, Muthama; Smith, Gideon (African Biodiversity & Conservation, 2026)
Background: The International Botanical Congress takes place more or less every six years. In the week preceding this conference, a meeting of the Nomenclature Section is held to consider proposals, both published and from the floor, to amend the International Code of Nomenclature for algae, fungi, and plants. Objectives: To report on the most significant outcomes of the deliberations that took place during, and decisions taken at, the Nomenclature Section and the final plenary session of the XXth International Botanical Congress that was held in Madrid, Spain, in July 2024. Methods: Decisions relevant to workers on South African algae, fungi and plants are summarised from the published reports of the relevant Permanent Nomenclature Committees and the General Committee, as well as from the published report of congress action. Results: This contribution is a summary of the most important decisions taken at the Nomenclature Section meeting and International Botanical Congress in Madrid, specifically highlighting those outcomes that are important for South African phycologists, mycologists and botanists.